2019
DOI: 10.3390/su11102870
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Riparian Forest Fragmentation and Biological Indicators of Streams

Abstract: Anthropogenic activities, such as land use and land cover modifications in riparian areas, can alter the degree of fragmentation of riparian vegetation, lead to the degradation of stream habitats, and affect biological communities in the streams. The characteristics of the riparian forests can modify the condition of stream environments and the transporting mechanisms of materials, sediments, nutrients, and pollutants loaded from the watersheds. This study aimed to examine the relationships between forest frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 162 publications
(205 reference statements)
3
28
0
Order By: Relevance
“…These results suggested that biological conditions in streams were better when riparian areas were covered with more forested area, contained larger forest patches, and the patches were located near riparian areas. These results confirmed the findings of a previous study, which suggested better biological condition with less fragmentation of riparian forests at a 500-m scale [8]. Thus, fragmentation of riparian forests was clearly negatively associated with biological condition of streams.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These results suggested that biological conditions in streams were better when riparian areas were covered with more forested area, contained larger forest patches, and the patches were located near riparian areas. These results confirmed the findings of a previous study, which suggested better biological condition with less fragmentation of riparian forests at a 500-m scale [8]. Thus, fragmentation of riparian forests was clearly negatively associated with biological condition of streams.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, fragmentation of riparian forests was clearly negatively associated with biological condition of streams. The biological condition of a stream was generally better if riparian forests were less fragmented, regardless of riparian scale, in accordance with recent studies [1,3,8]. As discussed by Yirigui et al (2019) and others (e.g., References [1,120]), more fragmented riparian forests may not provide the benefits of intercepting rainfall, lowering run-off speed, and increasing infiltration into soils and uptake time by plants typical of riparian areas.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations